2018
DOI: 10.1002/cam4.1622
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab maintenance improves overall survival in follicular lymphoma: A retrospective nationwide real‐world analysis from Taiwan Cancer Registry Database

Abstract: Follicular lymphoma (FL) is the most frequent indolent lymphoma in Western countries, but it is less frequent in Asia. Several trials have demonstrated the progression‐free benefit of rituximab maintenance for FL patients in Western countries. However, the overall survival (OS) benefits and effectiveness of rituximab maintenance in Asian FL patients remain uncertain. We utilized the Taiwan Cancer Registry Database and the National Health Insurance Research Database to investigate the roles of rituximab mainten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 24 publications
(49 reference statements)
1
11
0
Order By: Relevance
“…Both were analogous to those observed previously in Chinese FL patients and several Western cohorts [ 4 , 8 , 9 ]. We found that rituximab-based induction therapy ( R i ) followed by rituximab maintenance ( R m ) resulted in the best outcomes (both PFS and OS), consistent with the findings from another real-world study in Chinese population [ 10 ]. R i only was superior to Rm only (Fig.…”
supporting
confidence: 90%
“…Both were analogous to those observed previously in Chinese FL patients and several Western cohorts [ 4 , 8 , 9 ]. We found that rituximab-based induction therapy ( R i ) followed by rituximab maintenance ( R m ) resulted in the best outcomes (both PFS and OS), consistent with the findings from another real-world study in Chinese population [ 10 ]. R i only was superior to Rm only (Fig.…”
supporting
confidence: 90%
“…Maintenance therapy is a known effective strategy in prolonging remission for patients with NHL after induction therapy or stem-cell transplantation. For example, the clinical value of rituximab maintenance in treatment of FL has been demonstrated in several real-world studies in the United States, 14 Taiwan, 15 and Czech Republic. 16 Unfortunately, data on the use of maintenance therapy in low-grade lymphomas were not gathered in the HOLA study, with the exception of Argentina where rituximab maintenance was reported as the most common treatment for DLBCL at first or at second relapse (n = 11 of 74, 14.9% and n = 4 of 18, 22.2%, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Advances in the diagnosis and management of follicular lymphoma (FL) -most notably the introduction of rituximab -have considerably improved the survival of patients with FL over the past decades [1][2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%